2021
DOI: 10.1111/trf.16324
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of platelets treated with riboflavin and UV light and stored at −80°C for 1 year

Abstract: Background The combination of pathogen reduction technologies (PRTs) and cryopreservation can contribute to building a safe and durable platelet (PLT) inventory. Information about cryopreserved riboflavin and UV light‐treated PLTs is scarce. Study Design and Methods Twenty‐four buffy coat (BC) PLT concentrates were grouped into 12 type‐matched pairs, pooled, and divided into 12 non‐PRT‐treated control units and 12 riboflavin and UV light PRT‐treated test units. Both were cryopreserved with 5% DMSO and stored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
3
6
1
Order By: Relevance
“…11,14 One study reported TEG-MA values of 50-60 mm for products stored up to 6 months and ±40 mm for 12 month À80°C stored DTC. 43 Compared to published data the TEG-MA in our diluted samples was low (38-53 mm) but still higher compared to plasma and supernatant (25-29 mm). It has been shown previously that the 2000 G supernatant of DTC contain mostly platelet fragments and microparticles.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…11,14 One study reported TEG-MA values of 50-60 mm for products stored up to 6 months and ±40 mm for 12 month À80°C stored DTC. 43 Compared to published data the TEG-MA in our diluted samples was low (38-53 mm) but still higher compared to plasma and supernatant (25-29 mm). It has been shown previously that the 2000 G supernatant of DTC contain mostly platelet fragments and microparticles.…”
Section: Discussioncontrasting
confidence: 81%
“…Most studies use diluted samples with a platelet count of 200-300 Â 10 9 plt/L to study coagulation characteristics and TEG-MA of diluted DTC is 50-60 mm, 10,12,14,16,17,43 only a few report values below 50 mm. 11,14 One study reported TEG-MA values of 50-60 mm for products stored up to 6 months and ±40 mm for 12 month À80°C stored DTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tandem CPPs demonstrated faster mean R‐times compared with standard CPPs in both years, indicating a consistent and superior hemostatic quality for tandem CPPs over prolonged cryopreservation. For both CPP types, faster mean clotting times were observed in Y1 compared with Y2, although regardless of CPP type, year, and postthaw time points, mean R‐times observed were primarily under 4 min, and well within the two‐minute range even for tandem CPPs cryopreserved for up to 27 months at immediate postthaw, which are considerably faster R‐times among those reported irrespective of preparation methods, ranging from 3 to 11 min 20,26–34 . From two studies with longitudinal aspects that explored the time to clot initiation of thawed CPPs after 9 and 12 months of cryopreservation, 26,33 slight increments of R‐times have been observed over the first 6 months, but reduced after 9‐ and 12‐months respectively, hence a clear trend was not established.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have demonstrated the antioxidant function of riboflavin (Tang et al., 2014), and show that an altered riboflavin level causes spermatozoa morphological and bioenergetic defects in mice (Kuang et al., 2021). Riboflavin has recently been used to assist cryopreservation of platelets (Jimenez‐Marco et al., 2021). However, their functions in boar sperm are not well known.…”
Section: Discussionmentioning
confidence: 99%